An Assessment of the Impact of Public Debts on Development in Nigeria (2003-2020) - Oluwayemisi, Alli-Momoh Betty; Shawai Akinsanmi, Fatima Jummai; Rotimi, Oladele; Adekunle, Adediran Rasheed (Acta Universitatis Danubius. Œconomica, 2022)
The aim of the research was to determine the influence of Nigeria's public debt on the country's development. It especially looked at the link between the human development index, per capita income, growth rate, and public debt in Nigeria from 2003 to 2020, as well as the relationship between per capita income and public debt. The quantitative research design was used in this investigation. Important information about the under-studied variable was gathered from the Debt Management Office (2020) and the UNESCO Institute of Statistics (2020), and data was analyzed using the regression model developed by the University of Edinburgh. It was discovered by the research team, among other things, that there is co-integration (a long-run link) between the variables in the model. The t-statistics of -2.297997 with a p-value of 0.0388 indicate that there is a negative and significant relationship between foreign debt and the human development index, the t-statistics of 2.557340 with a p-value of 0.0239 indicate that there is a positive and significant relationship between foreign debt and per capital income, and the t-statistics of -0.658730 with a p-value of 0.5216 indicate that there A total of 4.109504 with a Prob.(F-statistic) of0.029617 for the f-statistics indicates that all of the explanatory factors have a statistically significant influence on foreign debt in both the short and long term. According to the findings of the research, there is a statistically significant association between public debt and development in Nigeria, depending on the variable of interest rate used. A similar recommendation was made in the study that the government should improve the efficiency and effectiveness of public debt management, citing the negative and significant influence of the human development index on both long-term and short-term development, as well as the negative and insignificant influence of foreign debt on development in Nigeria, which is a clear indication of ineffective public debt management practices in the country. Additionally, the component governments of Nigeria should minimize their public borrowing since it has a substantial negative impact on the long-term growth of the nation.